The views of Botswana adults towards support during childbirth - Doreen Kgokgothwane; Anna Nolte (AOSIS, 2002)
The positive effect of support during labour is well documented in the literature. Opsomming Die positiewe effek van ondersteuning tydens baring is goed gedokumenteer in die literatuur. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.